Pernoud & Clin, Joan Of Arc - Her Story - Kolbaba, Tia (Teaching History: A Journal of Methods, 2003)
Jeremy Adams here presents a revision and translation of one of Regine Pernoud’s magisterial works about Joan of Arc-this one researched and written with Marie-Veronique Clin, and titled, in its original French, simply Jeanne d’Arc (Paris, 1986). If Adams had produced only the translation, he would have done the English-reading public a great service, for the narrative, the argument, and "the battery of data" presented by Pernoud and Clin are invaluable. He has, however, done much more than translate: He has updated bibliography and "filmography," revised the text substantively at points, and provided a new introduction (called "Prelude"), which concisely and lucidly outlines the crucial context of the Hundred Years’ War and the Great Schism.